RETROSPECTIVE EVALUATION OF ASA CLASSIFICATION’S PREDICTIVE ABILITY OF POSTOPERATIVE COMPLICATIONS IN PATIENTS ADMITTED TO INTENSIVE CARE UNIT AFTER MAJOR ABDOMINOPELVIC SURGERY - Emre Sertaç Bingül; Ayşe Hızal; Başar Erdivanlı; Hızır Kazdal (Sabiad)
Objective: The American Society of Anaesthesiologists Physical Status Score (ASA) is a useful tool for indicating the need for intensive care unit (ICU) monitoring in postoperative patients. However, physician misclassification can lead to unnecessary bed occupancy and increased costs. This study examined the relationship between preoperative ASA scores and complications following major abdominopelvic surgery. Materials and Methods: Patients who underwent postoperative monitoring in a tertiary ICU between November 2016 and February 2019 for semi-urgent and urgent major abdominopelvic surgery were evaluated. Data related to morbidity and mortality were analysed, including acute postoperative complications (hypotension, bleeding, desaturation, prolonged intubation, failed weaning, acute kidney injury, cardiac arrest, exitus), length of ICU stay, recurrent ICU admissions, overall mortality incidence, and 30-day mortality incidence.Results: A total of 122 patients who underwent gastrointestinal, gynaecological, and urological surgeries were retrospectively analysed. Patients were grouped as ASA II (N=59), ASA III (N=45), and ASA IV (n=18). Overall complication rates among the groups did not differ. The exitus rate was significantly higher in ASA IV (p=0.022). Similarly, the duration of ICU stay, recurrent ICU admissions, and 30-day mortality were significantly higher in ASA IV (p<0.05). When patients were grouped as semi-urgent (n=87) and urgent (n=35), respiratory complications such as prolonged intubation, desaturation, and failed weaning, as well as ICU stay and 30-day mortality rates were higher in urgent cases (p<0.001). No exitus was observed in the semi-urgent oncological surgeries in the ICU. Conclusion: No difference in respiratory complications was observed in the postoperative ICU follow-up of ASA IV major abdominal surgery patients compared with other ASA groups. However, both respiratory complications and mortality rates were significantly higher in the urgent cases. The low rate of complications in semi-urgent oncological surgeries can be explained by the optimal preoperative surgical preparation.